1983
DOI: 10.1007/bf00313494
|View full text |Cite
|
Sign up to set email alerts
|

The nosological position of Fisher's syndrome (Ophthalmoplegia, Ataxia and Areflexia)

Abstract: Fisher's syndrome was studied in six patients, one of whom was an 11-year-old girl, and the nosological position of this neuro-ophthalmological disorder was reviewed. The clinical features of the ophthalmoplegia in these cases were reported as secondary to a transient inflammatory lesion in the mid-brain; this was demonstrated in one of the cases by an enhancing area on CT scan. This mid-brain localization could explain not only the classical Fisher's triad but also many variations of the syndrome. The overlap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
0
1

Year Published

1984
1984
2007
2007

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 36 publications
2
15
0
1
Order By: Relevance
“…Some published case reports describe MFS cases associated with evidence of brainstem or cerebellar lesions [9, 13, 34, 35, 36, 37, 38, 39], while others revealed normal findings [40, 41, 42]. In our study, the results of those patients who had brain CT or MRI examinations with or without contrast enhancement were all within normal limits.…”
Section: Discussionsupporting
confidence: 58%
See 2 more Smart Citations
“…Some published case reports describe MFS cases associated with evidence of brainstem or cerebellar lesions [9, 13, 34, 35, 36, 37, 38, 39], while others revealed normal findings [40, 41, 42]. In our study, the results of those patients who had brain CT or MRI examinations with or without contrast enhancement were all within normal limits.…”
Section: Discussionsupporting
confidence: 58%
“…The results have been controversial. Although some studies revealed no evidence of affection of the peripheral nerves [9, 11, 12, 13], most studies revealed peripheral nerve involvement such as abnormalities in distal motor latencies, motor conduction velocities, sensory conduction velocities, F wave latencies and H reflexes [19, 20, 21, 22, 23, 24, 25, 26, 27, 28, 29, 30, 31, 32, 33, 34]. Three out of our 10 patients had abnormal electrophysiological findings.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although CNSlesions have been suggested in addition to peripheral lesions based on the clinical symptoms of Fisher's syndrome (12,13), only two cases (14,15) showed a CNS lesion on CT, and one on MRI (16). Electrophysiologically, only a few cases (17)(18)(19) showed prolonged III-V inter-peak latency by BAEP and N13-N19 inter-peak latency by SEP. Prolongation of the inter-peak latencies, waves III-V of BAEPs and N13-N20 of SEPs indicated a CNSlesion in the present patient (20).…”
Section: Discussionmentioning
confidence: 99%
“…Fisher's syndrome -ophthalmoplegia, ataxia and areflexia -is generally considered a variant of GuillainBarre's syndrome [ 1 ]. We describe a case of Fisher's syn drome with a positive blood and spinal fluid serology for Campylobacter jejuni.…”
Section: Introductionmentioning
confidence: 98%